Beyond the jump: A scoping review of external training load metrics in volleyball - Rebelo, A.; Pereira, J. R.; Nakamura, F. Y.; Valente-dos-Santos, J. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Volleyball is a complex sport involving multifaceted movements and high-velocity actions, leading to diverse external training loads (ETLs) that have profound implications for player performance and injury risk.